DIGITAL DIDACTICS AS A NEW MODEL IN THE THEORY OF EDUCATION - Sagan, Olena; Yakovleva, Svitlana; Anisimova, Elena; Balokha, Alona; Yeremenko, Halyna (Revista Inclusiones, 2020)
Rapid changes in society connected with the qualitative transformation of informational and educational environment provoke the study and development of a new tendency in pedagogics, in particular in the theory of education. The article explains the necessity of transition to a new digital model of didactics, suggests its structure and approaches to its realization. The author’s vision of new principles, methods, means and forms of organization of modern education are presented in the article. The study of the level of teachers’ awareness of digital didactics principles and their real readiness to work in the conditions of informational educational environment has shown a low level of the formation of corresponding competences among teachers. As teacher’s qualities are transformed due to the transition from teaching to engineering of educational activity, the article states the main e-teacher’s qualities: informational resources analyst, content designer and designer of education and evaluation methods. Their formation helps to realize e-didactics idea, in which educational resource is a system-forming element. Given e-didactics structure illustrates the way educational resource can serve as content, tasks for the formation of corresponding competences and means of control of education quality. Padagogy Wheel is considered to be a means of web-resources selection for any level of knowledge. Teachers’ questionnaire has shown that their knowledge, skills and will to use web-resources (for example, Padagogy Wheel) in the organization of educational activity is at 30 % mark that requires considerable attention of pedagogical community. One of the ways of solving this problem consists in the creation and extensive testing of open educational resources dedicated to implementation of digital didactics.